Family Psychological Resistance from Batobo Cultural Perspective - Yantri Maputra; Lady Diana Yusri; Meria Susanti; Qolbi Khoiri (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2023)
This research aims to look at the cultural values of batobo, one of the Minangkabau cultures, in building family psychological resistance. The research method used qualitative approach with a descriptive phenomenological design. Data was collected through group interviews with 2 batobo groups and in-depth interviews with 3 community leaders selected through purposive sampling techniques. Data analysis using Nvivo 10.0 software. The results show that the batobo cultural values obtained in building family psychological resistance are: (i) form good individual characteristics such as flexibility, cohesiveness, (ii) make members have a favorable view of the future, (iii) live a more meaningful life by feeling happy with what they have, and (iv) have religious beliefs. These results indicate that batobo culture can increase people's psychological resistance. These results can encourage the community to continue to maintain batobo culture so that it can become an approach to creating a society that has psychological resistance.